Three-dimensional electrolytic copper foil titanium anode

By using a three-dimensional electrolytic copper foil titanium anode in the production of electrolytic copper foil, and using a mesh catalytic electrode combined with a three-dimensional porous material, the problem of mechanical size deviation of the traditional plate-shaped titanium anode is solved, and the quality of the copper foil and the service life of the anode are improved. At the same time, energy consumption is reduced.

CN119332311APending Publication Date: 2025-01-21JIANGYIN ANCAN ELECTROCHEM EQUIP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411223772.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Traditional plate-shaped titanium anodes have mechanical dimensional offset problems in the production of high-quality electrolytic copper foils, which affects its performance and service life.

Method used

A mesh catalytic electrode is combined with a three-dimensional porous material to prepare an electrolytic copper foil titanium anode with a three-dimensional structure. Through the composite structure of the electrocatalytic anode, the three-dimensional filler, and the supporting rib plate, an anode with efficient electrolyte diffusion and enhanced mechanical properties is formed. .

Benefits of technology

It improves the quality of copper foil products, reduces energy consumption, extends the service life of the anode, and further improves the performance of the anode by increasing electrocatalytic activity and oxidation resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332311A_ABST
    Figure CN119332311A_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional electrolytic copper foil titanium anode which comprises an electro-catalysis anode, a three-dimensional filling piece, a first supporting rib plate and a second supporting rib plate. The first supporting rib plate and the second supporting rib plate are welded to the arc-shaped base, and a plurality of openings arranged in a comb shape are formed in the second supporting rib plate. The second supporting rib plates are sequentially arranged at intervals, the first supporting rib plates are arranged on the outer sides of the second supporting rib plates respectively, the second supporting rib plates divide the first supporting rib plates into a plurality of arc-shaped partitions, and the three-dimensional filling pieces are arranged in the arc-shaped partitions. And the arc-shaped partitions can allow the electrolyte to circulate mutually through the openings. The electrolytic copper foil titanium anode with a three-dimensional structure is prepared by compounding the net-shaped catalytic electrode and the three-dimensional porous material, the electrolyte diffusion is improved, the concentration polarization is reduced, the copper foil product quality is improved, the effective area of the anode is increased, the current density is reduced, the cell voltage is reduced, the energy consumption is reduced, and the service life of the anode is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium anode preparation, and in particular to a three-dimensional electrolytic copper foil titanium anode. Background Art

[0002] Copper foil is the basic material of the electronics industry and the main raw material for making printed circuit boards (PCBs), copper clad laminates (CCLs) and lithium batteries. As electronic information products tend to be more high-performance and circuit boards become more multi-layered and dense, copper foil not only requires thinner thickness, but also has higher physical and chemical indicators. In particular, high-quality electrolytic copper foil plays a pivotal role in the development of the electronic information industry. The improvement of copper foil quality mainly depends on the progress of process technology and supporting equipment technology. As we all know, the key equipment of copper foil equipment is electrolytic foil machine, surface treatment machine and related testing equipment, as well as sewage treatment equipment. Among them, the electrolytic foil machine and surface treatment machine are directly related to the production quality of copper foil.

[0003] Electrolytic copper foil has become the main method of raw foil production. The electrolytic device for electrolytic production of copper foil is called a raw foil machine. The raw foil machine is provided with mutually adapted cathode rollers and anode tanks, and a titanium anode is installed in the anode tank. The working principle of the raw foil machine is: the raw foil unit is composed of cathode rollers and anode tanks, the anode tank body is connected to the positive output end of the DC power supply, and the cathode roller is connected to the negative output end of the DC power supply. When the copper sulfate electrolyte enters the anode tank body, an electric field is formed between the cathode and cathode. Under the action of the electric field, copper ions migrate to the surface of the cathode roller and deposit evenly. The deposited thin copper is called copper foil. Under the action of the electric field, copper ions continuously deposit to the cathode roller to form copper foil. The copper foil is peeled off from the cathode roller and rolled on another roller. In this way, the continuous production of copper foil is realized under the continuous circulation of the electrolyte.

[0004] With the increasing requirements on the quality and output of copper foil used in the manufacture of lithium batteries, the plating solution system has become more complex and the current density has become higher and higher, which has resulted in the service life of the anode, one of the main consumables of electrolytic copper foil, becoming increasingly shorter and its performance cannot be fully utilized.

[0005] The traditional electrolytic copper foil electrode is a plate-shaped titanium anode. It is difficult to ensure high precision in the processing of its substrate. After multiple high-temperature oxidations during coating preparation, the mechanical dimensions of the substrate are further offset, affecting its performance and service life.

[0006] In view of the above, it is necessary to propose a three-dimensional electrolytic copper foil titanium anode to solve the above problems. Summary of the invention

[0007] The purpose of the present invention is to overcome the defects in the prior art, use a mesh catalytic electrode and a three-dimensional porous material to prepare an electrolytic copper foil titanium anode with a three-dimensional structure, so as to achieve the purpose of improving the quality of copper foil products, reducing energy consumption and increasing service life.

[0008] To achieve the above-mentioned object, the technical solution of the present invention is as follows: a three-dimensional electrolytic copper foil titanium anode, comprising an electrocatalytic anode, a three-dimensional filler, a first supporting rib plate and a second supporting rib plate; A plurality of first support ribs and second support ribs are arranged between the arc-shaped base of the anode tank of the raw foil machine and the electrocatalytic anode. The first support ribs and the second support ribs are welded to the arc-shaped base of the anode tank of the raw foil machine. The second support ribs are provided with a plurality of openings arranged in a comb shape. A plurality of second support ribs are arranged in sequence at intervals, and the first support ribs are respectively arranged on the outer sides of the plurality of second support ribs. The second support ribs separate the first support ribs into a plurality of arc-shaped partitions, and a three-dimensional filling piece is arranged in each arc-shaped partition, and the openings between each arc-shaped partition allow electrolyte to flow through each other.

[0009] Furthermore, the electrocatalytic anode is a titanium-based oxide coating electrode with a thickness of 1-3 mm.

[0010] Further, the titanium-based oxide coating electrode is coated with one or more of the following oxide coatings: Oxide coating 1: Tantalum oxide coating; Oxide coating 2: ruthenium oxide coating; Oxide coating three: platinum oxide coating; Oxide coating four: iridium oxide coating; Oxide coating five: iridium tantalum oxide coating.

[0011] Furthermore, the titanium-based oxide coating is at least two of oxide coating one, oxide coating two, oxide coating three, oxide coating four, and oxide coating five.

[0012] Furthermore, the titanium-based oxide coating preparation liquid is: Preparation solution 1: Tantalum pentachloride and hydrochloric acid are dissolved in n-butanol at a molar ratio of tantalum to hydrochloric acid of 10:1-8:1; Preparation solution 2: ruthenium trichloride and hydrochloric acid are dissolved in n-butanol at a molar ratio of tantalum to hydrochloric acid of 8:1-6:1; Preparation solution 3: chloroplatinic acid is dissolved in one or more mixed solvents selected from n-butanol, ethanol, isopropanol and pinene alcohol; Preparation Solution 4: Dissolve chloroiridic acid and hydrochloric acid in n-butanol at a molar ratio of tantalum to hydrochloric acid of 9:1-6:1; Preparation solution 5: dissolve chloroiridic acid, tantalum pentachloride and hydrochloric acid in n-butanol at a molar ratio of iridium, tantalum and hydrochloric acid of 7:3:1-8:2:1; Sequentially apply the preparation solutions one, two, three, four and five to the treated titanium surface 0-4 times, 0-2 times, 0-5 times, 0-18 times and 10-16 times respectively; The standing time is 20-40 minutes; The drying temperature is 110-130°C, and the drying and heat preservation time is 10-25 minutes; The oxidation temperature is 450-500°C, and the oxidation holding time is 15-30 minutes; The cooling is natural cooling to room temperature in air.

[0013] Furthermore, the three-dimensional filling piece is a titanium woven mesh, titanium felt or titanium foam, with a thickness of 1-8 mm.

[0014] Furthermore, the titanium woven mesh, titanium felt or titanium foam has an oxide coating on its surface.

[0015] Furthermore, the first supporting rib and the second supporting rib are both made of titanium.

[0016] The advantages and beneficial effects of the present invention are: First, the three-dimensional electrolytic copper foil titanium anode of the present invention adopts a mesh catalytic electrode and a three-dimensional porous material to prepare an electrolytic copper foil titanium anode with a three-dimensional structure, which improves electrolyte diffusion, reduces concentration polarization, improves the quality of copper foil products, increases the effective area of ​​the anode, reduces current density, reduces cell voltage and energy consumption, and extends the service life of the anode.

[0017] Secondly, the three-dimensional electrolytic copper foil titanium anode of the present invention increases the electrocatalytic activity and oxidation resistance by coating the electrocatalytic anode with at least two oxide coatings, thereby improving the copper foil product quality and the anode service life.

[0018] Third, a plurality of first supporting ribs and second supporting ribs are welded on the arc-shaped base of the anode tank of the foil production machine, and then the first supporting ribs and the second supporting ribs, the three-dimensional filling parts and the electrocatalytic anode are welded and stacked in sequence from bottom to top to form a gas diffusion layer, increase the oxygen evolution escape rate and improve the electrolysis efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic structural diagram of a three-dimensional electrolytic copper foil titanium anode of the present invention; Figure 2 Schematic diagram of the structure of the electrocatalytic anode in the present invention; Figure 3 It is a schematic diagram of the structure of the three-dimensional filling member in the present invention; Figure 4It is a structural schematic diagram of the first supporting rib plate in the present invention; Figure 5 It is a schematic structural diagram of the second supporting rib plate in the present invention; In the figure: 1. electrocatalytic anode; 2. three-dimensional filling member; 3. first supporting rib plate; 4. second supporting rib plate; 5. opening; 6. arc-shaped base. DETAILED DESCRIPTION

[0020] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0021] Embodiment 1: Electrocatalytic anode substrate treatment: Sandblasting: Place the degreased titanium material in a sandblasting machine for sandblasting. Use 100 mesh and 10 mesh room temperature brown corundum for sandblasting in turn.

[0022] Pickling: Blow away the residual sand from the titanium material after sandblasting, and place it in a hot pickling solution for pickling. The pickling solution contains one or more of sulfuric acid, hydrochloric acid, acetic acid and citric acid. The pickling solution temperature is 70-100°C and the pickling time is 70-150 minutes. Water washing: Wash the pickled titanium material with water; Drying: Dry the washed titanium material.

[0023] 3D Filler 2 Substrate Treatment: Pickling: Place the titanium woven mesh, titanium felt or titanium foam in a room temperature pickling solution for pickling. The pickling solution contains one or more of sulfuric acid, hydrochloric acid, acetic acid and citric acid. The pickling time is 10-25 minutes. Water washing: Wash the pickled titanium material with water; Drying: Dry the washed titanium material.

[0024] Example 2-1: Prepare the following 5 coating solutions: Preparation solution 1: Tantalum pentachloride and hydrochloric acid are dissolved in n-butanol at a molar ratio of tantalum to hydrochloric acid of 10:1; Preparation Solution 2: Ruthenium trichloride and hydrochloric acid are dissolved in n-butanol at a molar ratio of 8:1 between tantalum and hydrochloric acid; Preparation solution 3: chloroplatinic acid is dissolved in one or more mixed solvents selected from n-butanol, ethanol, isopropanol and pinene alcohol; Preparation Solution 4: Dissolve chloroiridic acid and hydrochloric acid in n-butanol at a molar ratio of tantalum to hydrochloric acid of 9:1; Prepare solution 5: dissolve chloroiridic acid, tantalum pentachloride and hydrochloric acid in n-butanol at a molar ratio of iridium, tantalum and hydrochloric acid of 7:3:1.

[0025] Example 2-2: Prepare the following 5 coating solutions: Preparation solution 1: Tantalum pentachloride and hydrochloric acid are dissolved in n-butanol at a molar ratio of tantalum to hydrochloric acid of 8:1; Prepare solution 2: ruthenium trichloride and hydrochloric acid, dissolve in n-butanol at a molar ratio of tantalum to hydrochloric acid of 6:1; Preparation solution 3: chloroplatinic acid is dissolved in one or more mixed solvents selected from n-butanol, ethanol, isopropanol and pinene alcohol; Preparation Solution 4: Dissolve chloroiridic acid and hydrochloric acid in n-butanol at a molar ratio of tantalum to hydrochloric acid of 6:1; Prepare solution 5: dissolve chloroiridic acid, tantalum pentachloride and hydrochloric acid in n-butanol at a molar ratio of iridium, tantalum and hydrochloric acid of 8:2:1.

[0026] Example 3-1: The preparation solutions 1, 3 and 5 prepared in Example 2-1 were sequentially coated on the electrocatalytic anode 1 substrate in Example 1, with the number of times being 4, 1 and 16 respectively; the standing time was 20 minutes; the drying temperature was 110°C, the drying and heat preservation time was 15 minutes, the oxidation temperature was 490°C, the oxidation and heat preservation time was 15 minutes, and the coating was naturally cooled to room temperature in air each time.

[0027] The preparation solution prepared in Example 2-1 was coated onto the titanium woven mesh in Example 1 4 times. The standing time was 10 minutes; the oxidation temperature was 470°C, the oxidation holding time was 15 minutes, and each time it was naturally cooled to room temperature in air.

[0028] Example 3-2: The preparation solutions 2, 4 and 5 prepared in Example 2-1 were sequentially coated on the electrocatalytic anode 1 substrate in Example 1, with the number of times being 4, 1 and 16 respectively; the standing time was 20 minutes; the drying temperature was 110°C, the drying and holding time was 15 minutes, the oxidation temperature was 470°C, the oxidation and holding time was 25 minutes, and the coating was naturally cooled to room temperature in air each time.

[0029] The preparation solution prepared in Example 2-1 was coated on the titanium felt in Example 1 4 times. The standing time was 15 minutes; the oxidation temperature was 490°C, the oxidation holding time was 25 minutes, and the titanium felt was naturally cooled to room temperature in air each time.

[0030] Example 3-3: The preparation solutions 3 and 4 prepared in Example 2-1 were sequentially coated on the electrocatalytic anode 1 substrate in Example 1, with the number of times being 5 and 18 respectively; the standing time was 10 minutes; the drying temperature was 120°C, the drying and heat preservation time was 15 minutes, the oxidation temperature was 500°C, the oxidation and heat preservation time was 20 minutes, and the coating was naturally cooled to room temperature in air each time.

[0031] The preparation solution prepared in Example 2-1 was coated on the foamed titanium in Example 1 for 5 times. The standing time was 10 minutes, the oxidation temperature was 490°C, the oxidation holding time was 20 minutes, and each time the coating was naturally cooled to room temperature in air.

[0032] Embodiment 3-4: The preparation solutions 3 and 4 prepared in Example 2-1 were sequentially coated on the electrocatalytic anode 1 substrate in Example 1, with the number of times being 5 and 18 respectively; the standing time was 10 minutes; the drying temperature was 120°C, the drying and heat preservation time was 15 minutes, the oxidation temperature was 500°C, the oxidation and heat preservation time was 20 minutes, and the coating was naturally cooled to room temperature in air each time.

[0033] The preparation solution prepared in Example 2-1 was coated on the titanium woven mesh in Example 1 for 5 times. The standing time was 10 minutes, the oxidation temperature was 490°C, the oxidation holding time was 20 minutes, and each time it was naturally cooled to room temperature in air.

[0034] Embodiment 3-5: The preparation solutions 3 and 4 prepared in Example 2-1 were sequentially coated on the electrocatalytic anode 1 substrate in Example 1, with the number of times being 5 and 18 respectively; the standing time was 10 minutes; the drying temperature was 120°C, the drying and heat preservation time was 15 minutes, the oxidation temperature was 500°C, the oxidation and heat preservation time was 20 minutes, and the coating was naturally cooled to room temperature in air each time.

[0035] The preparation solution prepared in Example 2-1 was coated on the titanium felt mesh in Example 1 for 5 times. The standing time was 10 minutes, the oxidation temperature was 490°C, the oxidation holding time was 20 minutes, and each time it was naturally cooled to room temperature in air.

[0036] Embodiment 3-6: The preparation solutions 3 and 4 prepared in Example 2-1 were sequentially coated on the electrocatalytic anode 1 substrate in Example 1, with the number of times being 5 and 18 respectively; the standing time was 10 minutes; the drying temperature was 120°C, the drying and heat preservation time was 15 minutes, the oxidation temperature was 500°C, the oxidation and heat preservation time was 20 minutes, and the coating was naturally cooled to room temperature in air each time.

[0037] The preparation solution prepared in Example 2-1 was coated on the titanium woven mesh in Example 1 for 5 times. The standing time was 10 minutes, the oxidation temperature was 490°C, the oxidation holding time was 20 minutes, and each time it was naturally cooled to room temperature in air.

[0038] Embodiment 4: The titanium anodes prepared in Example 3-1, Example 3-2, Example 3-3, Example 3-4, Example 3-5, and Example 3-6 were tested, and the specific test contents and results are as follows: (1) Strengthening life evaluation The electrocatalytic anode 1 is a three-dimensional titanium anode prepared in Example 3-1, Example 3-2, Example 3-3, Example 3-4, Example 3-5, and Example 3-6, the cathode is titanium, and the current density is 100 kA / m 2 , solution system 4mol / L H2SO4 solution, time for the voltage to rise by 5V from the initial voltage.

[0039] The experimental results show that Example 3-1, Example 3-2, Example 3-3, Example 3-4, Example 3-5, and Example 3-6 all have good accelerated strengthening lifespan, among which Example 3-1 is the best.

[0040] sample Strengthening life / h Example 3-1 1209 Example 3-2 997 Example 3-3 1154 Embodiment 3-4 1191 Embodiment 3-5 968 Embodiment 3-6 1176 (2) Slot voltage evaluation The anode is a three-dimensional titanium anode prepared by the electrode of Example 3-1, Example 3-2, Example 3-3, Example 3-4, Example 3-5, and Example 3-6, and the cathode is titanium. The current density is 7000 A / m 2 , the solution system is 1 mol / L sulfuric acid. The cell voltage of Example 3-4 is the lowest, followed by Example 3-1.

[0041] sample Slot voltage / V Example 3-1 4.5813 Example 3-2 4.6832 Example 3-3 4.5911 Embodiment 3-4 4.5722 Embodiment 3-5 4.6341 Embodiment 3-6 4.5816 The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A three-dimensional electrolytic copper foil titanium anode, characterized in that: It comprises an electrocatalytic anode (1), a three-dimensional filling member (2), a first supporting rib plate (3) and a second supporting rib plate (4); A plurality of first supporting ribs (3) and second supporting ribs (4) are arranged between an arc-shaped base (6) of an anode tank of a foil machine and an electrocatalytic anode (1); the second supporting ribs (4) are provided with a plurality of openings (5) arranged in a comb shape; a plurality of second supporting ribs (4) are arranged in sequence and at intervals, and first supporting ribs (3) are respectively arranged outside the plurality of second supporting ribs (4); the second supporting ribs (4) separate the first supporting ribs (3) into a plurality of arc-shaped partitions, and a three-dimensional filling piece (2) is arranged in each arc-shaped partition.

2. A three-dimensional electrolytic copper foil titanium anode according to claim 1, characterized in that: The electrocatalytic anode (1) is a titanium-based oxide coating electrode with a thickness of 1-3 mm.

3. A three-dimensional electrolytic copper foil titanium anode according to claim 2, characterized in that: The titanium-based oxide coating electrode is coated with one or more of the following oxide coatings: Oxide coating 1: Tantalum oxide coating; Oxide coating 2: ruthenium oxide coating; Oxide coating three: platinum oxide coating; Oxide coating four: iridium oxide coating; Oxide coating five: iridium tantalum oxide coating.

4. The three-dimensional electrolytic copper foil titanium anode according to claim 3, characterized in that: The titanium-based oxide coating is at least two of oxide coating one, oxide coating two, oxide coating three, oxide coating four, and oxide coating five.

5. A three-dimensional electrolytic copper foil titanium anode according to claim 3 or 4, characterized in that: The titanium-based oxide coating preparation liquid is: Preparation solution 1: Tantalum pentachloride and hydrochloric acid are dissolved in n-butanol at a molar ratio of tantalum to hydrochloric acid of 10:1-8:1; Preparation solution 2: ruthenium trichloride and hydrochloric acid are dissolved in n-butanol at a molar ratio of tantalum to hydrochloric acid of 8:1-6:1; Preparation solution 3: chloroplatinic acid is dissolved in one or more mixed solvents selected from n-butanol, ethanol, isopropanol and pinene alcohol; Preparation Solution 4: Dissolve chloroiridic acid and hydrochloric acid in n-butanol at a molar ratio of tantalum to hydrochloric acid of 9:1-6:1; Preparation solution 5: dissolve chloroiridic acid, tantalum pentachloride and hydrochloric acid in n-butanol at a molar ratio of iridium, tantalum and hydrochloric acid of 7:3:1-8:2:1; Sequentially apply the preparation solutions one, two, three, four and five to the treated titanium surface 0-4 times, 0-2 times, 0-5 times, 0-18 times and 10-16 times respectively; The standing time is 20-40 minutes; The drying temperature is 110-130°C, and the drying and heat preservation time is 10-25 minutes; The oxidation temperature is 450-500°C, and the oxidation holding time is 15-30 minutes; The cooling is natural cooling to room temperature in air.

6. The three-dimensional electrolytic copper foil titanium anode according to claim 1, characterized in that: The three-dimensional filling piece (2) is a titanium woven mesh, titanium felt or titanium foam, and has a thickness of 1-8 mm.

7. The three-dimensional electrolytic copper foil titanium anode according to claim 6, characterized in that: The titanium woven mesh, titanium felt or titanium foam has an oxide coating on its surface.

8. The three-dimensional electrolytic copper foil titanium anode according to claim 1, characterized in that: The first supporting rib plate (3) and the second supporting rib plate (4) are both made of titanium.